Biogenic polymer based patches for congenital cardiac surgery: future development of implants - Richert, Emma; Grefen, Linda; Zorin, Alexandra; Hubrich, Julian; Simon, Stefan; Sommerhoff, Christian P.; Hagl, Christian; Herz, Christopher; Obrist, Dominik; Hörer, Jürgen; Carrel, Thierry; Grab, Maximilian; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveDespite advancements in surgical techniques, many patients born with congenital heart defects (CHD) require repeated reinterventions due to the limitations of materials used in congenital cardiac surgery (CCS). Traditional biogenic polymers, such as bovine or equine pericardium, are prone to calcification, have limited durability, and fail to adapt to the growth of infants. This study aims to address these challenges by investigating bacterial cellulose (BC) as a promising material for CCS.MethodsVariability in patch quality from previous studies was addressed by refining the production protocol taking advantage of optical density (OD) measurements. After a 72 h incubation, patches were harvested and tested mechanically with burst pressure and uniaxial strain testing. BC's biomechanical properties were further explored by modifying nutrient concentrations, creating different media groups (N10, N30, N50). Hybrid patches combining BC with electrospun polyurethane (ESP-PU) were developed using a specially designed 3D-printed flask to ensure uniform coating and integration.ResultsThe initial bacterial concentration significantly influenced cellulose yield and growth rate, with static cultures outperforming shaken ones. Nutrient-enriched media (N10, N30, N50) produced cellulose with greater elasticity and strength compared to standard C-Medium, with stiffness correlating to nutrient concentration. Inflation tests showed that N10 and N30 samples withstood higher pressures than N50, which, despite being stiffer, performed worse under rapid inflation. All samples, however, maintained pressures above physiological levels. Scanning electron microscopy analysis confirmed effective BC coating of PU fibres without altering BC fibre orientation or bacterial activity.ConclusionBC patches demonstrated burst pressure resistance above 1,400 mmHg. BC's elasticity can be tailored, and in combination with ESP-PU, an innovative hybrid material can be produced, positioning BC as a promising biomaterial for future CCS implant development.